Nicotine and Amino Acids Binding, A Theoretical Studies - Huda N. Al-Ani (Journal of Global Pharma Technology, 2016)
The binding of twenty Amino Acids to Nicotine, has been studied theoretically by using (DFT) Density Functional Theory of (HF) type, as well as the semi-empirical method (PM3) calculations are carried out by (MOPAC) computational packages, to calculate the molecular orbital's energies and some molecules properties. The studied system was: Cysteine (Cys), Methionine (Met.) and Valine (Val.) with Nicotine. The optimized geometry of the complexes showed interaction between Nicotine and three Amino Acids molecules, Cysteine (Cys), Methionine (Met.) and Valine (Val.), the binding energies for these interaction were calculated, the binding energies for these interaction varies from -5.188 to -7.223 Kcal.mol-1. Which attributed to the formation of hydrogen bonding between the studied molecules as it agrees with IR- experimental data .Binding to proteins is an important determinant of the kinetics .Which restricts the unbound concentration and effects the distribution and diminution of it.Key words: Nicotine, Amino Acids, binding, Density Functional Theory (DFT).